Integrasi Pendidikan Karakter Dalam Perangkat Pembelajaran Pendidikan Agama Katolik di SMA Santo Bonaventura Madiun - Murlani Murlani (Universitas Muhammadiyah Malang, 2013)
The purposes of this research 1). to explain the integration of character education in developing of silabus, RPP, extracurriculer activities, 2) to explain the obstacle on the integration. (3) to explain the efforts to overcome the obstacle in the integration of character education of sets of Catholic learning in Sint Bonaventura Senior High School. Data are collected by interview, observation and documentation. The validity of datas use the analyzes of data use tehnique with interactive model that consist of component of collecting data, presentation of data and make conclusion. The results of the research point out 1) in integrating of character education in catholic education silabus suitable with the law of indonesian republic no. 20 in 2003 on article 3. character building as well is one of the principal esenci especially in religion and religion education as the only one of perfect media to make the civilized. 2) The integration of caracter education in sets of learning has with the obility of students in catolic education. Character in education the integration of character education can be habitualized and exsampled in formal and informal situation based on the ability of children without neglecting the exist norm.